Geochemistry of the Kola River and Lake Imandra, northwestern Russia - Pekka, Larisa (Luleå tekniska universitet, 2005)
The impact from mining and large-scale agricultural activities on levels and migration of metals within the Kola River and Lake Imandra has been studied in detail. Evaluation of the pollution status in the Kola River is based on sampling of the dissolved (<0.22 µm) and suspended (>0.22 µm) fractions and also metal accumulation in aquatic bryophytes on 12 sites along the Kola River and its tributaries during an annual cycle. In Lake Imandra the sampling of dissolved (<0.45 µm) and suspended (<0.45 µM) fractions from 18 sampling levels within the water column was performed on three sampling occasions. Also, a sediment core and porewater were sampled. Major and trace elements (Al, As, Ba, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sr and Zn), total and particulate organic carbon (TOC and POC), N and P were analysed. The work was performed in close co-operation with Russian and Finnish scientists. An important and surprising result from the analyses of both water and bryophyte samples is the relatively low overall contamination in the Kola River, much lower than was reported in previous studies. In comparison with Swedish and Finnish reference data from the Kalix and Näätämöjoki Rivers, only Cu and Ni are elevated. The concentrations of As, Cu, Mn, Mo and Ni in bryophytes and water were highest close to the mine areas, relatively low in the middle parts of the Kola River, and elevated at the river mouth. Evaluation of the sampling methods and the analytical results obtained from the parallel sampling occasions in the Kola River performed by the Murmansk Area Department for Hydrometeorology and Environmental Monitoring (MADHEM) and by Luleå University of Technology (LTU) clearly indicated contamination problems during the fieldwork and transportation of samples by Russian partners, which may explain high trace-metal concentration data for the Kola River obtained in previous monitoring programmes. Results from the Lake Imandra study demonstrate the dominant role of Mn redox cycling in controlling distribution of ...